3-in-1 technique applied to mixed CH4:CO2 gas hydrates (2019)
The 3-in-1 method was used to study hydrate morphology, kinetics and phase equilibria of hydrates formed in gas-dominated systems containing pure CH4, pure CO2, and two CH4:CO2 mixtures (80:20 and 30:70 on a molar basis). This technique offered high resolution imaging and a tight control of pressure and temperature. The same experimental temperatures were used for all gas compositions. Different pressures allowed to match subcoolings across mixtures, in the range of deltaTsub = 0.5 K to deltaTsub = 4.5. In addition, multiple driving forces were studied in a single experiment using temperature gradients across a single sample. Crystal morphology was found to be highly dependent on the CH4:CO2 molar ratio, and a higher dependence on the deltaTsub was observed for methane-rich hydrate morphology. The measured hydrate film growth rate increased with increasing CO2 content and increasing deltaTsub. Hydrate growth beyond the original droplet boundary ('halo') was observed for pure CO2 and the two mixtures, and it was found to be dependent on the CH4:CO2 molar ratio and deltaTsub. A stepwise dissociation was used to measured the H-L-V equilibrium temperature (THLV). The dissociation was carried out by setting a gradient along the slide, which allowed a close control of the H-L-V interface position.